2015
DOI: 10.1186/s12902-015-0013-6
|View full text |Cite
|
Sign up to set email alerts
|

Living with type 1 diabetes is challenging for Zambian adolescents: qualitative data on stress, coping with stress and quality of care and life

Abstract: BackgroundPsychosocial problems are common in patients with diabetes. However, data on psychosocial issues affecting patients with diabetes in Zambia are scarce. The present study explored sources of stress, stress coping strategies, stigma and perceived quality of life and care as experienced by adolescents living with Type 1 Diabetes in Zambia.MethodsSemi-structured interviews were carried out. Three groups of participants involving adolescents with Type 1 Diabetes (n = 10), caregivers (n = 8) and health pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
54
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 23 publications
8
54
0
5
Order By: Relevance
“…For example, the Lin et al (2008) study on Taiwanese individuals with T2DM found that some people believe diabetes is an infectious disease, and they stigmatize people with diabetes as contagious. Hapunda et al (2015) noted that in Zambia there is a fear of getting diabetes in a social setting. Therefore, some children who participated in a study mentioned that the community perceived them as "infectious" and some of their peers would deny playing with them because they may catch diabetes (Hapunda et al, 2015).…”
Section: Having a Contagious Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…For example, the Lin et al (2008) study on Taiwanese individuals with T2DM found that some people believe diabetes is an infectious disease, and they stigmatize people with diabetes as contagious. Hapunda et al (2015) noted that in Zambia there is a fear of getting diabetes in a social setting. Therefore, some children who participated in a study mentioned that the community perceived them as "infectious" and some of their peers would deny playing with them because they may catch diabetes (Hapunda et al, 2015).…”
Section: Having a Contagious Diseasementioning
confidence: 99%
“…It is estimated that, globally, 387 million people have diabetes; this number is expected to rise to 592 million by 2035 (International Diabetes Federation, n.d.). In response to a world pandemic of diabetes, it is crucial to consider that people living with diabetes are stigmatized by their illness (Abdoli, Ashktorab, Ahmadi, Parvizy, & Dunning, ; Anderson‐Lister & Treharne, ; Hapunda, Abubakar, Van de Vijver, & Pouwer, ; Kato, Takada, & Hashimoto, ; Schabert, Browne, Mosely, & Speight, ; Singh, Cinnirella, & Bradley, 2012), especially those living with T1DM (Abu Hassan et al., ; Jaacks, Liu, Ji, & Mayer‐Davis, ; Spencer, Cooper, & Milton, ; Vishwanath, ).…”
Section: Introductionmentioning
confidence: 99%
“…15 Depressive symptoms and diabetes distress have consistently demonstrated associations with lower engagement in T1D self-management, poorer glycemic outcomes, and lower quality of life, 16,17 and fear of hypoglycemia has mixed associations with diabetes outcomes. 15 Interpersonal diabetes-related burdens include stigma, [18][19][20] family conflict, 21,22 and insufficient parental involvement in diabetes selfmanagement, 23 which have been linked with suboptimal diabetes management and glycemic outcomes. 24,25 Some youth and families are more vulnerable to diabetes-related emotional burdens than others.…”
Section: Emotional Burdens Of Youth With T1dmentioning
confidence: 99%
“…Estudo internacional apresenta que as famílias desenvolvem estratégias de enfrentamento da doença, sendo a religião e a espiritualidade ferramentas fundamentais para o auxílio na aceitação da nova condição crônica (14) .…”
Section: Convivendo Com a Doença Do Filhounclassified